Employing modern audio technologies In the narrative of the cinematographic image (Journal of the College of Basic Education, 2022)
The importance of this study is due to its attempt to identify the technological development in the field of sound creativity, which began to invade the world cinema steadily and analyze a large area through the stages of working with modern systems and follow special techniques and treatments during the stages of pre-production, production and post-production in a degree commensurate with the technology required to implement the stages of production To obtain a tape or an audio stream that has dramatic and aesthetic effectiveness and meets all technical requirements. Using modern technological means. In workstations and with the help of electronic units and sound effects libraries (sound effects libraries), which is a collection of sounds preserved on a medium. And those means that work in the subsequent sound production stage